(Fe, Ni)9S8 Nanosheets on a Three‐Dimensional Conductive Substrate for Efficient Oxygen Evolution Reaction Electrocatalysis. Issue 4 (17th February 2021) - Shi, Bu‐Yan; Huang, Yuan; Jiang, Li‐Wen; Chowdhury, Mahabubur; Liu, Hong; Wang, Jian‐Jun
Abstract: The development of low‐cost and high‐efficiency electrocatalysts for the oxygen evolution reaction (OER) is essential for a number of applications in the field of energy conversion and storage. Herein, we present an efficient OER electrocatalyst in the form of thin (Fe, Ni)9 S8 nanosheets (FNS NSs) anchored on a three‐dimensional (3D) conductive substrate of Fe/Fe3 O4 nanoislands/carbon cloth (Fe NIs/CC). The resulting electrode exhibits an impressive OER performance with a low overpotential of 147 mV at 10 mA cm −2 and a Tafel slope of 29.8 mV dec −1 in 1 M KOH alkaline solution. The enhanced performance is ascribed to the thin nanosheet structure with ample active sites, the high conductivity of the substrate, and the 3D structure, which endow the electrode with a large specific surface area and more catalytic active sites. Study of the kinetic process reveals that the incorporation of Fe from the substrate can reduce the kinetic barrier of OER, allowing for a faster reaction rate. Abstract : On‐site : An efficient oxygen evolution reaction (OER) electrocatalyst in the form of thin (Fe, Ni)9 S8 nanosheets anchored on a 3D conductive substrate of Fe/Fe3 O4 nanoislands/carbon cloth is designed. The resulting electrode exhibits an impressive OER performance with a low overpotential of 147 mV at 10 mA cm −2 and a Tafel slope of 29.8 mV dec −1 in 1 M KOH alkaline solution. The enhanced performance is ascribed to the thin nanosheet structure with ample active sites, the high conductivity of the substrate, and the 3D structure, which endow the electrode with a large specific surface area and more catalytic active sites.